1981
DOI: 10.1002/jpln.19811440107
|View full text |Cite
|
Sign up to set email alerts
|

Mineral transformations by fungi in culture and in soils

Abstract: Although micro‐organisms are regarded as the principal agents of mineral cycling in soils, the role of bacteria has generally been emphasized, while that of fungi has been neglected. Fungi are able to transform the majority of elements in vitro but whether they play an important role in soil is as yet unknown. There is sufficient circumstantial evidence from soil studies to suggest that fungi may under certain conditions nitrify and oxidize reduced forms of sulphur. Their role in denitrification and sulphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Properties of the site other than soil reaction, such as humus and clay content or litter quality, may possibly determine which hypothesis is correct for acid softs. Knowledge of heterotrophic nitrifying bacteria and fungi has been reviewed [10,11]. Heterotrophic nitrification has also been identified in a forest soft [12].…”
Section: Introductionmentioning
confidence: 99%
“…Properties of the site other than soil reaction, such as humus and clay content or litter quality, may possibly determine which hypothesis is correct for acid softs. Knowledge of heterotrophic nitrifying bacteria and fungi has been reviewed [10,11]. Heterotrophic nitrification has also been identified in a forest soft [12].…”
Section: Introductionmentioning
confidence: 99%
“…Heterotrophic S oxidation is in many ways analogous to heterotrophic nitrification. Both processes involve fungi and heterotrophic bacteria, and although the involvement of these organisms has long been recognized, their role was overlooked as soon as chemoautotrophic Nand S-oxidizing bacteria were discovered (15,19).…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of heterotrophic microorganisms, including actinomycetes (21), heterotrophic bacteria (8,12,13), and fungi (18,19,20), are able to oxidize various forms of inorganic S. Wainwright and Killham (20) recently showed that the soil fungus Fusarium solani (Martius Saccards) can oxidize So to S2032-, S4062-, and S042in vitro and in autoclaved and nonsterile soils, but did not demonstrate whether or not the process is enzymatic.…”
mentioning
confidence: 99%